Hematolymphoid Lesions of the Sinonasal Tract - Crane, Genevieve M. (Semin Diagn Pathol, 2015)
Various hematolymphoid lesions involve the sinonasal tract, including aggressive B, T, and NK-cell neoplasms; myeloid sarcoma; low grade lymphomas; indolent T-lymphoblastic proliferations; and Rosai-Dorfman disease. Differentiating aggressive lymphomas from non-hematopoietic neoplasms such as poorly differentiated squamous cell carcinoma, olfactory neuroblastoma, or sinonasal undifferentiated carcinoma may pose diagnostic challenges. In addition, the necrosis, vascular damage and inflammatory infiltrates which are associated with some hematolymphoid disorders can result in misdiagnosis as infectious, autoimmune or inflammatory conditions. Here, we review hematolymphoid disorders involving the sinonasal tract including their key clinical and histopathologic features.